2023
DOI: 10.1126/scitranslmed.add4666
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex epigenome editing of MECP2 to rescue Rett syndrome neurons

Abstract: Rett syndrome (RTT) is an X-linked neurodevelopmental disorder caused by loss-of-function heterozygous mutations of methyl CpG-binding protein 2 ( MECP2 ) on the X chromosome in young females. Reactivation of the silent wild-type MECP2 allele from the inactive X chromosome (Xi) represents a promising therapeutic opportunity for female patients with RTT. Here, we applied a multiplex epigenome editing approach to reactivate MECP2 from Xi in RTT human embryonic stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Our work builds upon other studies that have used targeted DNA demethylation editing to restore silenced gene expression in stem cells and neurons, including BDNF , FMR1 , MECP2 , and the imprinted Dlk1-Dio3 locus (Liu et al, 2016, Liu et al, 2018, Qian et al, 2023, Kojima et al, 2022). These studies have demonstrated that targeting a dCas9-TET1 fusion to the methylated promoter of the silenced gene is sufficient to activate its expression.…”
Section: Discussionmentioning
confidence: 97%
“…Our work builds upon other studies that have used targeted DNA demethylation editing to restore silenced gene expression in stem cells and neurons, including BDNF , FMR1 , MECP2 , and the imprinted Dlk1-Dio3 locus (Liu et al, 2016, Liu et al, 2018, Qian et al, 2023, Kojima et al, 2022). These studies have demonstrated that targeting a dCas9-TET1 fusion to the methylated promoter of the silenced gene is sufficient to activate its expression.…”
Section: Discussionmentioning
confidence: 97%
“…Transduction of hESC derived neurons with dCas9-Tet1/sgRNA proved that demethylation of the MECP2 promoter reactivated the wild type allele located on the Xi (82% of protein expression). Moreover, direct epigenome editing of neurons, carrying on Xi MeCP2 exon 3 fused with GFP and its methylated promoter and on Xa MeCP2 exon 3 fused with tdTomato, showed a moderate reactivation of MeCP2-GFP (17,7% of protein expression) without affecting the expression of other genes on both X chromosomes ( Qian et al, 2023 ). Although precise DNA methylation editing of MECP2 displayed encouraging results, further validation in in vivo animal models of RTT is essential for the translational value of this approach.…”
Section: Reactivation Of the Inactive X Chromosomementioning
confidence: 99%
“…93 A recent study described that reactivating the MeCP2 gene locus in the silenced but normal X-chromosome by demethylation rescues abnormalities in Rett neurons. 94 Separate studies have described that suppressing MeCP2 expression using antisense oligonucleotides and other genetic methods can reduce behavioral defects in a transgenic mouse model of MeCP2 duplication syndrome. 95,96 However, in these studies, the line of MeCP2 used exhibits very mild symptoms relative to patients with MeCP2 duplication syndrome.…”
Section: The Principalsmentioning
confidence: 99%